2022
DOI: 10.1115/1.4054060
|View full text |Cite
|
Sign up to set email alerts
|

Association of Collagen, Elastin, Glycosaminoglycans, and Macrophages With Tissue Ultimate Material Strength and Stretch in Human Thoracic Aortic Aneurysms: A Uniaxial Tension Study

Abstract: Objective: Fibre structures and pathological features, e.g., inflammation and glycosaminoglycan (GAG) deposition, are the primary determinants of aortic mechanical properties. This study is designed to quantify the association of tissue ultimate strength and stretch with the structural percentage of different components, in particular, GAG, and local fibre structure. Methods: Thoracic aortic aneurysm (TAA) tissues from 8 patients were collected. Ninety-six tissue strips of thickened intima, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this figure, the sample has minimal collagen presence and exhibits a uniform distribution of elastin. This may be attributed to the intimal layer being richer in elastin fibers than in collagen 9 and the similarity between the elastin and collagen spectra. 17 A variation in the attenuation coefficient throughout the sample indicates a morphological change in different regions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this figure, the sample has minimal collagen presence and exhibits a uniform distribution of elastin. This may be attributed to the intimal layer being richer in elastin fibers than in collagen 9 and the similarity between the elastin and collagen spectra. 17 A variation in the attenuation coefficient throughout the sample indicates a morphological change in different regions.…”
Section: Resultsmentioning
confidence: 97%
“…3 Other pathologies of the aorta include aneurysm, which is an abnormal increase in the diameter of this artery and often can lead to an aortic rupture with a fatal outcome for the patient; 4 atherosclerosis involving lipids deposition within the aorta; 3 stenosis refers to an issue with the aortic valve; 5 aortic insufficiency concerning a problem in the control of the blood flow; 3 and a bicuspid aortic valve as a congenital issue of the aortic valve. 6 Many studies on the evolution and forecast of CVDs-related diseases are based on a compositional analysis of the aortic wall [7][8][9][10] including analysis of the morphology of its layers. 10,11 Since the evolution of these diseases occurs over many years, it poses a challenge to have animal models to replicate them.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the vasa vasorum is mainly found in the adventitia, but also exists in the outer layers of the media to feed the aorta. This vascular bed is actually the main source of the inflammatory cells in the outer wall media/adventitia [ 9 ]. Crosslinks of elastic fiber-ECM, SMC-ECM and SMC-SMC maintains normal strength of thoracic aortic walls, suppress immune cell infiltration, and prevent the thoracic aorta from weakening.…”
Section: Structure Of Normal Thoracic Aortic Walls and Basic Pathophy...mentioning
confidence: 99%
“…It was reported that the glycosaminoglycan (GAG) deposition was associated positively with the local collagen fibre dispersion and negatively with ultimate strength in the circumferential direction [39]. In fact, GAG is highly negatively charged and thus sequester water and contribute directly to the compressive, rather than tensile stiffness of the artery [40,41].…”
Section: The Relationship Between Materials Constants and Fibre Micro...mentioning
confidence: 99%